Disease prevention in family medicine - Kamaruzaman, Nor Azam; Shalihin, Mohd Shaiful Ehsan (IIUM Press, 2022)
Preventive care activities are essential core elements in family medicine as they are often incorporated into family physician practice either in patient care or in clinical settings. Examples are when the doctor measures the blood pressure of a patient complaining of skin rash to screen for hypertension or an accompanying person checking his own weight and height at the self-examination corner in the clinic. Preventive care activities are most offered regularly as scheduled care such as in childhood immunisation programmes and periodic health examinations.